The ppGpp synthetase gene (relA) of Streptomyces coelicolor A3(2) plays a conditional role in antibiotic production and morphological differentiation. - Chakraburtty, R (1997)
Deletion of most of the coding region of the ppGpp synthetase gene (relA) of Streptomyces coelicolor A3(2) resulted in loss of ppGpp synthesis, both upon entry into stationary phase under conditions of nitrogen limitation and following amino acid starvation during exponential growth, but had no effect on growth rate. The relA mutant, which showed continued rRNA synthesis upon amino acid depletion (the relaxed response), failed to produce the antibiotics undecylprodigiosin (Red) and actinorhodin (Act) under conditions of nitrogen limitation. The latter appears to reflect diminished transcription of pathway-specific regulatory genes for Red and Act production, redD and actII-ORF4, respectively. In addition to the changes in secondary metabolism, the relA mutant showed a marked delay in the onset and extent of morphological differentiation, resulting in a conspicuously altered colony morphology.